Apixification on immature tooth traumatized with crown-root fracture: case report - Freire, Thatiana Cristino (2022)
Dental trauma is a health problem with high frequency in children and young adults. They are associated to psychological, functional and aesthetics consequences. Pulp necrosis is one of the main consequences after a dental trauma and implies failure in the root development of newly erupted permanent teeth, which therefore remain thin walls and open apex. The objective of this study was to describe a treatment option that allows the development of the root apex and the strengthening of the apical walls in immature teeth that present pulp necrosis after trauma. Apexification with a single application of calcium hydroxide was used as technique. This study concluded that calcium hydroxide apexification is a low cost alternative, easily applicable in the clinical routine and that presents high success rates in the treatment of immature traumatized teeth.